Tingkat Serangan Brontispa Longissima (Gestro) (Coleoptera: Chrysomellidae) pada Kelapa (Cocos Nucifera) Varietas Genjah dan Varietas Dalam di Kabupaten Solok: english - Simamora, Kiki Fajrina; Yunisman, Yunisman; Winarto, Winarto (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2018)
The attack of Brontispa longissima has spread to almost all coconut plantations in Indonesia. This study aimed to determine the attack level of B.longissima on dwarf and tall varieties and the number of fruit in Solok Regency. A survey with purposive random sampling was done. The parameters observed were the percentage of plants attacked, the percentage of midribs attacked, and the number of the coconut fruit. The results showed that the highest percentage of coconut attacked by B. longissima occurred on the tall variety (83.34%) in Gunung Talang Subdistrict, the highest percentage of midribs attack occurred on tall variety (12.67%) in X Koto Singkarak Subdistrict. There was a negative close correlation between the percentage of leaves attacked and the number of coconuts.